2000
DOI: 10.1128/jb.182.21.5990-5996.2000
|View full text |Cite
|
Sign up to set email alerts
|

Swarming of Pseudomonas aeruginosa Is Dependent on Cell-to-Cell Signaling and Requires Flagella and Pili

Abstract: We describe swarming in Pseudomonas aeruginosa as a third mode of surface translocation in addition to the previously described swimming and twitching motilities. Swarming in P. aeruginosa is induced on semisolid surfaces (0.5 to 0.7% agar) under conditions of nitrogen limitation and in response to certain amino acids. Glutamate, aspartate, histidine, or proline, when provided as the sole source of nitrogen, induced swarming, while arginine, asparagine, and glutamine, among other amino acids, did not sustain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
781
6
10

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 752 publications
(832 citation statements)
references
References 52 publications
35
781
6
10
Order By: Relevance
“…As expected with the cells growing more slowly on glycerol, swarming was slower but the final results were essentially the same (data not shown). This is in contrast to swarming in E. coli (Harshey & Matsuyama, 1994) or Pseudomonas aeruginosa (Kohler et al, 2000), which is abolished by growth on glycerol. In the presence or absence of tryptophan or lysine, the swarming rate and patterns obtained were indistinguishable.…”
Section: The Swarming Pattern Is Not Dependent Upon the Presence Of Gmentioning
confidence: 75%
“…As expected with the cells growing more slowly on glycerol, swarming was slower but the final results were essentially the same (data not shown). This is in contrast to swarming in E. coli (Harshey & Matsuyama, 1994) or Pseudomonas aeruginosa (Kohler et al, 2000), which is abolished by growth on glycerol. In the presence or absence of tryptophan or lysine, the swarming rate and patterns obtained were indistinguishable.…”
Section: The Swarming Pattern Is Not Dependent Upon the Presence Of Gmentioning
confidence: 75%
“…Swarming is dependent on the combination of the polar flagellum, type IV pili and rhamnolipid production (Caiazza et al, 2005;Kohler et al, 2000). This type of motility is almost completely absent in the oxyR mutant grown on CAA medium (Fig.…”
Section: Oxyr Is Required For Swarming Motility and Rhamnolipid Produmentioning
confidence: 99%
“…Previously, it was reported that swarming motility is enhanced by the addition of biosurfactants and that mutants of Serratia liquefaciens defective in biosurfactant production have no swarming ability (19,21). Indeed, swarming motility in the ⌬orf3 mutant was enhanced in both SWM and MMMF plates with 0.5% agar (Fig.…”
Section: Vol 188 2006mentioning
confidence: 99%